2018
DOI: 10.1021/acs.chemrev.7b00695
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Investigations of Carbon Dioxide Gas in Metal–Organic Frameworks: Insights into Molecular Motion and Adsorptive Behavior

Abstract: Solid-state nuclear magnetic resonance (SSNMR) methods have been routinely used for the characterization of both the structure and the dynamics of metal organic frameworks (MOFs), a collection of porous media investigated for potential applications in carbon capture technologies, selective separation of small molecules, and catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 83 publications
2
99
2
2
Order By: Relevance
“…15,16 Furthermore, guest molecules are likely to desorb from MOF pores under the high-vacuum condition ($10 À6 mbar) of the TEM at room temperature (Supplemental Experimental Procedures). Therefore, current studies rely on ensemble measurements using X-ray/neutron diffraction, 17,18 nuclear magnetic resonance, 19 or theoretical simulations. 20 However, the structural information obtained by these methods is averaged over bulk particles.…”
mentioning
confidence: 99%
“…15,16 Furthermore, guest molecules are likely to desorb from MOF pores under the high-vacuum condition ($10 À6 mbar) of the TEM at room temperature (Supplemental Experimental Procedures). Therefore, current studies rely on ensemble measurements using X-ray/neutron diffraction, 17,18 nuclear magnetic resonance, 19 or theoretical simulations. 20 However, the structural information obtained by these methods is averaged over bulk particles.…”
mentioning
confidence: 99%
“…[35] Solid-state NMR spectroscopy was frequently utilized for the exploration of the chemical structures, dynamic behavior, and host-guest interaction of MOFs. [36][37][38][39][40][41][42][43][44] To investigate the chemical composition of these activated UiO-66-X (X = -H, -2COOH, -SO 3 H) and multivariate functionalized UiO-66-X samples, 1 H and 13 C MAS NMR experiments were conducted. Figure 2 shows the 1 H MAS and 13 C CP/MAS NMR spectra of dehydrated UiO-66, UiO-66-SO 3 H, UiO-66-2COOH and multivariate functionalized UiO-66-X samples.…”
Section: Resultsmentioning
confidence: 99%
“…MOFs are potent materials not only for gas storage but also for separation, e.g., removal of CO 2 from other gases like methane. Various 13 C NMR investigations of CO 2 adsorbed on MOFs were reported meanwhile as can be found in the recent review by Witherspoon et al 48 Interaction of CO 2 with open Mg sites in Mg-MOF-74 revealed a line shape characteristic of chemical shi anisotropy but with a reduced width compared to that of rigid CO 2 . 49 It was concluded that adsorbed CO 2 jumps between different open metal sites.…”
Section: Examples For Host-guest Interaction Studiesmentioning
confidence: 97%